Internalization Analysis of Islamic Values in Organization Culture at Nabila Bakery - Alifia Rosyida Pratiwi (IAIN Salatiga, 2021)
The purpose of this research is to provide an overview and knowledge about the Internalization of Islamic Values in corporate culture in Nabila Cake, Bakery Pastry. The aim specifically to obtain the results of the analysis of internalization of Islamic values applied by the company to employees and the corporate environment, and also the form of corporate culture used by the company to manage human resources in it. In this research, the author using the qualitative method. The object that used in this research was including every aspect that accorded to the Islamic Values at Nabila Cake, Bakery Pastry. In this study, the results shown that in the company Nabila Cake, Bakery Pastry stated that the corporate culture is a reflection of the company’s identity. Islamic values that internalized through the organizational culture such as Ihsan and Itqan. The internalization of Islamic values in the corporate culture in Nabila has been given a comprehensive role, both in the corporate environment, as well as in the personal life of each individual in it.